Analisis Pembelajaran Seni Anak Usia Dini melalui Kegiatan Finger Painting - Bunga Chantika; Windi Dwi Andika; Lia Dwi Ayu Pagarwati (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2024)
When children learn, they often have difficulty using crayons, which hinders their ability to color. Therefore, we need a medium that allows children to express their artistic talents more widely. One solution is to use finger painting as a learning medium. Finger painting is a painting activity that uses the fingers as a tool. This research aims to describe AUD art learning through finger painting. The type of research used is descriptive with qualitative methods. This type of research examines an object and searches for facts with the correct interpretation. The research results show that learning art for AUD through finger painting can stimulate children's creativity in expressing their ideas in the form of works of art, besides that finger painting can be used as an effective and efficient alternative method for improving artistic abilities in early childhood.